THE PERILS OF JARGONS: HOW ILLUSION OF KNOWLEDGE OBSCURES TRUE TEACHER COMPETENCE - Henry Wijaya (LITERA, 2019)
Teacher competence is a crucial factor to the success of BIPA teaching and learning. In terms of pedagogy, a competent BIPA teacher naturally is not only proficient at theories, but also adept at materializing them into classroom instructions, to help students learn effectively. Nonetheless, trapped inside knowledge illusion of one’s own competence, a teacher might believe having grasped the latest development in language teaching, while in fact, although capable of reciting jargons smoothly, that teacher still teaches traditionally. This paper (re-)visits trends in modern language teaching, reflecting on which we have genuinely understood and fully implemented, and which still require our study. Ultimately, this paper expects to contribute to the larger discussion of how BIPA teacher competence should be defined and could be improved.           Keywords: teacher competence, language pedagogy, classroom practice, jargons, reflection